Preparation of Accounting Guidelines and Standard Operating Procedures for the Receipt and Expenditure Cycle of the Karya Mandiri Foundation - Muhammad Ardhian Anwar, Muhammad Ardhian Anwar (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze the cash receipt and expenditure cycle currently implemented at the Karya Mandiri Foundation. In addition, this study also aims to prepare accounting guidelines and standard operating procedures for the receipt and expenditure cycle of the Karya Mandiri Foundation. This study uses the Karya Mandiri Foundation as the object of research. This foundation is a social, religious, and humanitarian institution located in the Curug area, East Jakarta. This research is a project based research using the qualitative Research and Development (R&D) method. The development model in this study uses the (ADDIE) model limited to the Analysis, Design, and Development stages. The data collection method used in this study through several methods, namely observation of the research location, interviews with foundation administrators, and documentation. The data analysis method used in this study consists of data reduction, data presentation, and drawing conclusions. The results of this study are in the form of an accounting guideline module and Standard Operating Procedure (SOP) on the cash receipt and expenditure cycle of the Karya Mandiri Foundation. This accounting guideline will be a clear guide in recording and managing every cash receipt and expenditure transaction of the foundation. This guideline includes definitions, legal basis, account classification, and accounting treatment. Meanwhile, the Standard Operating Procedure (SOP) on the cash receipt and expenditure cycle of the foundation will be used by the foundation administrators in understanding the flow of the cash receipt and expenditure process, increasing transparency and accountability, and efficiency in the foundation’s operations. This SOP includes detailed steps starting from the planning process, implementation, to reporting.